2014
DOI: 10.1124/jpet.114.214189
|View full text |Cite
|
Sign up to set email alerts
|

Trovafloxacin Enhances Lipopolysaccharide-Stimulated Production of Tumor Necrosis Factor-αby Macrophages: Role of the DNA Damage Response

Abstract: Trovafloxacin (TVX) is a drug that has caused idiosyncratic, druginduced liver injury (IDILI) in humans. In a murine model of IDILI, otherwise nontoxic doses of TVX and the inflammagen lipopolysaccharide (LPS) interacted to produce pronounced hepatocellular injury. The liver injury depended on a TVX-induced, small but significant prolongation of tumor necrosis factor-a (TNF) appearance in the plasma. The enhancement of TNF expression by TVX was reproduced in vitro in RAW 264.7 murine macrophages (RAW cells) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Moreover, predicting idiosyncratic hepatotoxicity reactions has been a formidable challenge. The LPS model has been employed to evaluate IDILI successfully for several drugs in humans, such as trovafloxacin, sulindac, halothane, chlorpromazine, monocrotaline, ranitidine, diclofenac, and amiodarone in toxicological experiment assessment on the basis of the inflammatory stress hypothesis (Waring et al, 2006; Shaw et al, 2010; Roth and Ganey, 2011; Poulsen et al, 2014). The previous research constructed Heshouwu idiosyncratic hepatotoxicity, based on LPS animal models, has manifested Heshouwu could induce acute liver injury in rats cotreated with LPS approximate to the clinical equivalent dose, and the animal model should make it possible to assess idiosyncratic hepatotoxicity of the herb (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, predicting idiosyncratic hepatotoxicity reactions has been a formidable challenge. The LPS model has been employed to evaluate IDILI successfully for several drugs in humans, such as trovafloxacin, sulindac, halothane, chlorpromazine, monocrotaline, ranitidine, diclofenac, and amiodarone in toxicological experiment assessment on the basis of the inflammatory stress hypothesis (Waring et al, 2006; Shaw et al, 2010; Roth and Ganey, 2011; Poulsen et al, 2014). The previous research constructed Heshouwu idiosyncratic hepatotoxicity, based on LPS animal models, has manifested Heshouwu could induce acute liver injury in rats cotreated with LPS approximate to the clinical equivalent dose, and the animal model should make it possible to assess idiosyncratic hepatotoxicity of the herb (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of IDILI is very complex, among which inflammation response plays a critical role. The inflammatory stress hypothesis has provided some of the first animal models of idiosyncratic hepatotoxicity (Roth and Ganey, 2011; Poulsen et al, 2014). Nontoxic dose of LPS precipitate modest inflammatory responses in mammals, resulting in increased susceptibility to toxicity from numerous hepatotoxic chemicals (Deng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a cell-free system, TVX inhibited eukaryotic topoisomerase-IIα (Poulsen et al 2014), which is involved in DNA replication and cell cycle regulation (Larsen et al 1996). This can create a replication stress that initiates events involved in cell death and inhibition of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…7), suggesting the parent dronedarone is more likely than its metabolites to interfere with topoisomerase IIα expression. It has been reported that some drugs and naturally occurring compounds inhibit topoisomerases II, leading to DNA damage and liver toxicity (Chen et al 2013; Poulsen et al 2014; Zhang et al 2015). In agreement with these studies, our current study highlights the role of topoisomerase IIα in drug-induced liver toxicity.…”
Section: Discussionmentioning
confidence: 99%